2021
DOI: 10.3390/brainsci11050621
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Autistic Traits, Ruminative Thinking, and Suicidality in a Clinical Sample of Subjects with Bipolar Disorder and Borderline Personality Disorder

Abstract: (1) Background: Previous literature reported in both subjects with Borderline personality disorder (BPD) and Bipolar disorder (BD) higher levels of autistic traits, linked to a greater suicidality risk. The aim of this study was to evaluate and compare the presence of autistic traits in a sample of individuals with BD or BPD, with a specific focus on suicidality. (2) Methods: We recruited two clinical samples of subjects (BPD and BD) and a control group without a diagnosis according to DSM-5 (CTL). Subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 59 publications
2
55
0
1
Order By: Relevance
“…This case is also in line with the extensive literature that highlighted a high prevalence of suicide attempts, suicidal thoughts and behaviors among ASD patients or in subjects with autistic traits [ 31 33 , 48 51 ]. It is worth mentioning that both the patients reported the highest percentage scores on the AdAS Spectrum Restrictive Interest and Rumination and in Inflexibility and adherence to routine domains.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This case is also in line with the extensive literature that highlighted a high prevalence of suicide attempts, suicidal thoughts and behaviors among ASD patients or in subjects with autistic traits [ 31 33 , 48 51 ]. It is worth mentioning that both the patients reported the highest percentage scores on the AdAS Spectrum Restrictive Interest and Rumination and in Inflexibility and adherence to routine domains.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the relevance of the subthreshold autism spectrum lies in the fact that, according to a large number of studies, not only full-blown ASD, but also milder presentations or even subthreshold autistic traits could actually interfere with general functioning, representing a significant risk factor for the development of suicidal ideation [ 31 , 46 , 47 ]. Taking into account the growing number of studies that highlighted the presence and relevance of autistic traits in clinical populations not affected by full-blown ASD [ 31 33 , 36 38 , 48 ], it has also been suggested the hypothesis that different types of psychiatric disorders may be underlain by an ASD-like neurodevelopmental alteration, whose interaction with the environment and life events may lead to different psychopathological trajectories [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the validation study [1], the AdAS Spectrum questionnaire demonstrated an excellent reliability and a strong convergent validity with other scales employed in this field, such as the Autism-Spectrum Quotient Test [22] and the e Ritvo Autism and Asperger Diagnostic Scale 14-item version [23]. The AdAS Spectrum has been used, in recent years, within numerous studies focusing on the autism spectrum both in clinical and in nonclinical settings [24][25][26][27][28][29][30][31][32][33].…”
Section: The Adult Autism Subthreshold Spectrummentioning
confidence: 99%
“…The CS would therefore represent a complementary tool, and not a substitute for the diagnosis of catatonia made according to the criteria of the DSM-5, investigating, in addition to nuclear symptoms, all those subthreshold, atypical and partial manifestations that often precede the diagnosis of the disorder by years. This spectrum approach has previously been applied, successfully, to other mental disorders ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%